Optimalisasi Implementasi Sistem Informasi Manajemen dalam Penerimaan Peserta Didik Baru di MTs Negeri 2 Kota Jambi - Pinasti, Sekar Ayu; Armida, Armida; Zas Pendi, Hamdi (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2026)
This study examines the implementation of a Management Information System (MIS) in the New Student Admission process at MTs Negeri 2 Jambi City. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation, and analyzed using reduction, display, and conclusion drawing techniques. The findings reveal that MIS implementation has improved administrative efficiency, accelerated the selection process, and enhanced transparency. However, challenges remain, including limited digital literacy among parents and technical constraints such as network instability. From the Technology Acceptance Model (TAM) perspective, user acceptance is influenced by perceived usefulness and ease of use, with higher acceptance among internal stakeholders. The evaluation based on the CIPP model confirms the system’s effectiveness across context, input, process, and product dimensions. Furthermore, the integration of Islamic values—amanah, ‘adl, and hisab—reinforces ethical governance. The study concludes that MIS functions as a strategic tool for improving educational management and service quality.